Reduction of the Survival of the Soilborne Pathogen Phytophthora palmivora on Theobroma cacao Pods Through the Application of Trichoderma spp. (TERRA LATINOAMERICANA, 2026)
In Ecuador, Phytophthora palmivora is an important pathogen af fecting the cultivation of Theobroma cacao. The survival of this microorganism depends largely on its ability to reproduce in pods lef t on the soil. This study evaluated fourteen native isolates of Trichoderma spp. with the aim of reducing the pathogen’s survival and thereby decreasing the potential inoculum present in the soil. The research was conducted in the Microbiology area of the Rumiología laboratory at the Universidad Técnica Estatal de Quevedo (Ecuador). Trichoderma and P. palmivora strains were obtained from institutional collections and cultured on Potato Dextrose Agar and V8 Juice Agar media, respectively. Dual cultures of biocontrol agents and the pathogen were performed to calculate the pathogen’s growth inhibition percentage. Additionally, the isolates were classified according to their antagonistic activity using standard scales. The two best-performing biocontrol strains were selected to conduct pod assays to evaluate their ef fect on infection and reproduction of artificially inoculated P. palmivora. Moreover, the impact of these strains on the reproductive capacity of the pathogen was assessed in naturally infected pods. Strains TR8-N and TR19-N demonstrated superior results, exhibiting over 90% inhibition and high antagonistic capacity. Microscopic observations revealed alterations in pathogen hyphae and evidence of mycoparasitism. In pod assays, those treated with TR8-N showed no symptoms following artificial pathogen inoculation. Both TR19-N and TR8-N reduced pathogen inoculum production on the surface of naturally infected pods. These results indicate that at least two native isolates evaluated could be applied on af fected pods to reduce pathogen inoculum in cacao cultivation soils.
Keywords: antagonism; biocontrol; infection; inoculum; zoospores